The great workplace how to build it, how to keep it, and why it matters - Burchell, Michael, 1967- (Jossey-Bass, 2011)
"For 20 years, the Great Place to Work® Institute has been developing the annual ranking of the best companies to work for in the US and in 39 countries around the world. In the US, the ranking is published by FORTUNE and is best known as the FORTUNE 100 Best Companies to Work For. In 2010, the list included among its finalists: SAS, Google, REI, Scripps Health, Hoar Construction, DreamWorks Animation, Zappos.com, Salesforce.com, Cisco, Marriott Interntional, American Express, Mayo Clinic, Microsoft. Drawing on the Institute's wide and deep body of knowledge acquired in the process of producing this ranking, Institute senior consultant Michael Burchell and research fellow Jennifer Robin reveal that what separates the great from the good companies to work for is the leader's ability to create Trust, Pride and Camaraderie in their companies. THE GREAT WORKPLACE explains the concept of a Great Place to Work--defined as one in which employees trust the people they work for, have pride in what they do, and enjoy the people they work with--and demystifies the Institute's Great Place to Work model, developed in 1984 and validated through its enduring resonance in both the United States and in 40 countries around the world. It also answers the fundamental question, "What is the business value of creating a great workplace?" and brings the definition of a Great Place to Work alive with anecdotes, best practices, and quotes from employees working at the best workplaces in the US (and ranked in the list). Companies featured in the book include: General Mills, Google, Gore, Microsoft, PricewaterhouseCoopers, SAS, Scripps Health, Wegman's and S.C. Johnson. As organizations grapple with the complexity and challenges of leveraging human capital in today's hyper-competitive work world--and as the Institute increases its presence across the world--THE GREAT WORKPLACE will be the "must read" source for understanding the essential ingredients in and trends of great places to work"--